Adaptasi Pendatang Luar Aceh Terhadap Bahasa Dalam Komunikasi Antarbudaya - Siti Maghfirah Fitri (Sadida Islamic Communications and Media Studies, 2022)
Every individual will interact through communication according to the language they have. There are separate obstacles for migrants from outside Aceh to interact with the people and the environment who have their own culture, language and customs. One of the obstacles for these migrants is the language barrier. This study aims to find out how immigrants from outside Aceh adapt to the language with the community and the surrounding environment in intercultural communication. The research method uses a qualitative approach with a phenomenological study with the research subjects being informants who are migrants from outside Aceh who live in the Acehnese community. The theory in this study is the theory of cross-cultural adaptation. The results of this study were in the form of an adaptation process to the language carried out by Mrs. N P and Mrs. Er, who directly practiced the Acehnese language in daily communication. Thus it can be concluded that adaptation to language affects the lives of outsiders from Aceh.